Data structure uniqueness in Python programming language / Jamal Othman - Othman, Jamal (Unit Penerbitan JSKM, 2023)
Python is categorized as general-purpose language which means it can be applied to a variety of problems or not specialized to a specific area. Python is a powerful programming language which supports the creation of application systems, penetration of security testing and conduct complex data analysis on huge volume of data (data science). Hence, Python helps the programmer to develop the application faster because the syntaxes are almost like and simpler than C, C++ and Java programming languages. Among of the uniqueness of Python programming language is the implementation of its data structure. Data structures as implemented in the Python programming are easier to be organized or manipulated. Set, List, Tuple and Dictionary are among the most important built-in data structure in Python. These data structures have been simplified as compared to array and linked list data structures as used in C or C++. Each data structure in Python has its own strengths and characteristics in terms of mutable or immutable which means the ability to modify or change the value of data structure element’s. Versatility of Python, make the Pythonistas are highly demanded amongst IT companies if they know better the usage of different kind of data structures in manipulating bulks of huge data to generate very valuable results.